Influence of the Microalgae Chlorella Vulgaris on the Adsorption of Zinc and Iron from the Effluents of the Chungar Mine, Yauli - Peru - Zevallos Alcántara, Enori Leslie (2024)
The mining industry in central Peru is the most important activity and one of the main contributors to the country's economy, however, it usually causes harmful impacts to the environment through mining tailings, the release of inor- ganic compounds, discharges of acid effluents to water sources that alter the structure of the ecosystem. Therefore, the objective is to evaluate the influence of the Chlorella vulgaris microalgae on the adsorption of Zn and Fe metals from effluents from the Chungar mine, Yauli. The design of the research was experi- mental with a duration of 14 days, where we worked with samples of the mining effluent and microalgae strains at the laboratory level, using a completely random block design with factorial arrangement of 2 x 4 with 3 replications, being a total of 12 experimental units including the control, where a treatment was applied with doses of 50 ml, 100 ml and 200 ml of Chlorella vulgaris. During the exper- imentation, the results show that the optimal dose of the microalgae is 200 ml, since the concentrations of the metals were considerably reduced compared to their initial amount, the microalgae strains were exposed to environmental con- ditions that facilitated their growth, being their capacity of adsorption of Fe (62.16%) greater than Zn (26.98%). Concluding, that strains of Chlorella vul- garis microalgae significantly influence the adsorption of metals Zn and Fe.